The Phonetic Dimension of Qur’anic Readings in the Framework of Modern Phonetics - Asmaa Younis (PT. Student Rihlah Indonesia, 2026)
This This study examines the phonetic characteristics of Qur’ānic recitation (Qirāʾāt) through the perspective of modern phonetic science, with a particular focus on articulatory and acoustic analyses. The research explores how the rules of tajwīd, which govern the precise articulation of sounds in Qur’ānic recitation, correspond to phonetic phenomena studied in contemporary linguistics. Key areas of investigation include the articulation of consonants, the lengthening and quality of vowels, assimilation and nasalization patterns, as well as prosodic features such as intonation, rhythm, and pause. By applying phonetic tools to the study of Qirāʾāt, the research demonstrates that tajwīd rules are not only rooted in devotional practice but also embody systematic phonetic principles. Consonantal articulation ensures that sounds remain distinct and semantically accurate, vowel lengthening preserves meaning by distinguishing between different lexical items, and prosodic features contribute to both clarity and the musicality of recitation. Acoustic analysis further reveals how precise sound production safeguards the Qur’ānic text from phonological distortion, ensuring its transmission with both accuracy and aesthetic beauty. The findings highlight the intricate relationship between phonetics and tajwīd, showing that correct recitation functions simultaneously as a linguistic safeguard, a spiritual practice, and an art form. This underscores the importance of accurate pronunciation in preserving the Qur’ān’s meaning, eloquence, and oral heritage. Beyond bridging tajwīd and modern phonetics, the study contributes to interdisciplinary scholarship by demonstrating how linguistic science can illuminate traditional Islamic knowledge and support pedagogical approaches in Qur’ānic studies.